Comparisons of doxycycline solution with talc slurry for chemical pleurodesis and risk factors for recurrence in South Korean patients with spontaneous pneumothorax. Issue 5 (18th April 2018) - Park, Eun Ha; Kim, Joo Hee; Yee, Jeong; Chung, Jee Eun; Seong, Jong Mi; La, Hyen Oh; Gwak, Hye sun
Abstract : Purpose: Talc slurry (TS) has been commonly used with high success rates in managing spontaneous pneumothroax (SP), but there were concerns of post-procedural complications. Alternatively, doxycycline solution (DS) was used successfully. This retrospective study aims to compare the effectiveness and safety between talc and doxycycline as a sclerosing agent and to investigate risk factors for recurrence in patients with SP. Methods: The review of medical records between January 2011 and December 2014 was conducted on 83 patients with SP who underwent pleurodesis with either TS (n=16) or DS (n=67). Recurrence and complications were compared between the DS and TS groups. Associations between recurrence after DS treatment and various factors were analysed. Results: Recurrence was significantly higher in the DS group than in the TS group (P=0.033), whereas complications were higher in the TS group than the DS group: fever was significantly higher in the TS group (P=0.001). Recurrences associated with doxycycline use were found significantly more often in patients with recurrent diagnosis of SP, height/weight ≥3.25 cm/kg and weight <55 kg. Conclusion: Talc was more effective without recurrence compared with doxycycline. Clinically insignificant fever associated with pleurodesis was more common with talc. Low weight, high height to weight ratio and recurrent diagnosis of SP were associated with higher recurrence after doxycycline treatment.